How the COVID-19 pandemic changed the Plastic Surgery activity in a regional referral center in Northern Italy. Issue 7 (July 2020) - Pignatti, Marco; Pinto, Valentina; Miralles, Maria Elisa Lozano; Giorgini, Federico A.; Cannamela, Giacomo; Cipriani, Riccardo
Abstract: The Covid 19 epidemic has modified the way that plastic surgeons can treat their patients. At our hospital all elective surgery was canceled and only the more severe cases were admitted. The outpatient department activity has been reduced also. We present the number and diagnoses of patients, treated as in- and out-patients, during seven weeks from the onset of the epidemic, comparing our activity from the lockdown of elective surgery with the numbers and diagnoses observed during the same weeks of last year. Finally we underline the importance of using telemedicine and web-based tools to transmit images of lesions that need the surgeon's evaluation, and can be used by the patient to keep in touch with a doctor during the distressing time of delay of the expected procedure.